2021
DOI: 10.1007/s11071-021-06615-9
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic analysis of 1-dof and 2-dof nonlinear energy sink with geometrically nonlinear damping and combined stiffness

Abstract: Nonlinear energy sink (NES) refers to a typical passive vibration device connected to linear or weakly nonlinear structures for vibration absorption and mitigation. This study investigates the dynamics of 1-dof and 2-dof NES with nonlinear damping and combined stiffness connected to a linear oscillator. For the system of 1-dof NES, a truncation damping and failure frequency are revealed through bifurcation analysis using the complex variable averaging method. The frequency detuning interval for the existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…7. NESs with nonlinear damping [147][148][149]: The nonlinear geometric damping has been firstly applied with NESs in [64,65]. However, the nonlinear damping and combined stiffness components are incorporated in the NES in [147] for studying the dynamical behavior of single and 2-DOF systems attached with this NES.…”
Section: Other Kinds or Modified Nessmentioning
confidence: 99%
See 1 more Smart Citation
“…7. NESs with nonlinear damping [147][148][149]: The nonlinear geometric damping has been firstly applied with NESs in [64,65]. However, the nonlinear damping and combined stiffness components are incorporated in the NES in [147] for studying the dynamical behavior of single and 2-DOF systems attached with this NES.…”
Section: Other Kinds or Modified Nessmentioning
confidence: 99%
“…NESs with nonlinear damping [147][148][149]: The nonlinear geometric damping has been firstly applied with NESs in [64,65]. However, the nonlinear damping and combined stiffness components are incorporated in the NES in [147] for studying the dynamical behavior of single and 2-DOF systems attached with this NES. It was concluded that incorporating nonlinear damping in the considered NES has enhanced the vibration mitigation performance compared with the case of only incorporating a linear damping.…”
Section: Other Kinds or Modified Nessmentioning
confidence: 99%
“…The vibration reduction performance of SPNES and CNES was also compared under harmonic excitation. Since the response of the LO is complex near the main resonance, the energy spectrum is introduced [30] , which is defined as follows: As shown in Fig. 9, when the harmonic excitation is weak, the vibration reduction performance of SPNES is better than that of CNES.…”
Section: Fig 7 Analysis Of Vibration Reduction Performance Of Spnes A...mentioning
confidence: 99%
“…This paper studies the dynamics of NES with geometrically nonlinear attenuation with a SDOF and 2 degrees of freedom. In a similar paper [24], the dynamics of 1-dof and 2-dof NES with nonlinear damping and combined stiffness connected to a linear generator is investigated. The vibration suppression effect of the proposed NES with nonlinear damping and combined stiffness is analyzed and verified by the energy spectrum, as well as shows that the 2-dof NES system demonstrates the best performance.…”
Section: Related Workmentioning
confidence: 99%